2017
DOI: 10.4330/wjc.v9.i3.261
|View full text |Cite
|
Sign up to set email alerts
|

Significance of inferior wall ischemia in non-dominant right coronary artery anatomy

Abstract: AIMTo investigate the relationship of inferior wall ischemia on myocardial perfusion imaging in patients with non-dominant right coronary artery anatomy.METHODSThis was a retrospective observational analysis of consecutive patients who presented to the emergency department with primary complaint of chest pain. Only patients who underwent single photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) were included. Patients who showed a reversible defect on SPECT MPI and had coronary angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Our study demonstrated additional evidence that SPECT MPI in detecting inferior/inferior-lateral wall ischemia has a statistically significant higher incidence of false positive studies with left or codominant coronary circulation compared to its right dominant counterpart. This finding was previously described in an observational study in which the authors hypothesized that the flow tracer in a left dominant or codominant circulation may show relatively decreased uptake in the inferior wall that might not be indicative of flow-limiting stenosis [ 3 ]. In addition, anatomical variation in vessel size might also be contributing to this observed phenomenon [ 3 ].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our study demonstrated additional evidence that SPECT MPI in detecting inferior/inferior-lateral wall ischemia has a statistically significant higher incidence of false positive studies with left or codominant coronary circulation compared to its right dominant counterpart. This finding was previously described in an observational study in which the authors hypothesized that the flow tracer in a left dominant or codominant circulation may show relatively decreased uptake in the inferior wall that might not be indicative of flow-limiting stenosis [ 3 ]. In addition, anatomical variation in vessel size might also be contributing to this observed phenomenon [ 3 ].…”
Section: Discussionsupporting
confidence: 61%
“…This finding was previously described in an observational study in which the authors hypothesized that the flow tracer in a left dominant or codominant circulation may show relatively decreased uptake in the inferior wall that might not be indicative of flow-limiting stenosis [ 3 ]. In addition, anatomical variation in vessel size might also be contributing to this observed phenomenon [ 3 ].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…When the optimal cutoff of rCFI was used to diagnose ischemia, the sensitivity was only 53%, but the speci city was 93%. One of the reasons for the low sensitivity is the presence of false positives in the inferior wall of the left ventricle on SPECT; that is, in the RCA territory 23 . In our study, the rCFI for the RCA ischemia depicted by SPECT (n = 7) was 0.81 ± 0.21.…”
Section: Discussionmentioning
confidence: 99%